Rotated hough filtering for automatically distinguishing the collagen bundles in the most superficial layer of articular cartilage - Duan, Xiaojuan; Wu, Jian Ping; Kirk, Thomas (Elsevier, 2013)
The structure of the collagen matrix in the most superficial layer of articular cartilage (AC) is particularly critical to the wear and tensile resistance of AC. Disruption of the collagen network leads to rapid wear of the articular surface, which is a major contributory factor of osteoarthritis. Interwoven fiber bundles have been observed in the most superficial layer of healthy AC under confocal microscopy, but gradually disappear with age and pathological change of AC. The image analysis techniques developed in this paper aimed to provide a quantitative description of the relationship between the presence of the fiber bundles in the lamina splendens and health status of AC. The result of this quantitative study confirmed the existence of fiber bundles in healthy AC, and the accuracy of the identified fiber bundles was up to 90%. With the development of confocal arthroscopy for imaging microstructure of AC without biopsy, the image analysis technique can aidto efficiently assess the physiological status of AC for orthopaedic clinics.